2010
DOI: 10.1097/rli.0b013e3181f10fe1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Adipose Tissue in Single Transverse Slices for Estimation of Volumes of Relevant Fat Tissue Compartments

Abstract: Axial MRI at the umbilical level allowed for a fast and reliable estimation, especially for VAT and TAT in a collective at risk for type 2 diabetes. WHR and BMI were found clearly worse in prediction of VAT volumes compared with single slice evaluation at the umbilical level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 46 publications
2
29
0
2
Order By: Relevance
“…The strength of association between anthropometric indices and VAT in our study is similar to that reported in other studies [32][36], although some studies reported lower correlation coefficients [21], [37][39]. The single best anthropometric predictor for the specific measures of both VAT and CAT appeared to be waist circumference in both sexes, although BMI showed almost equally strong univariate correlations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The strength of association between anthropometric indices and VAT in our study is similar to that reported in other studies [32][36], although some studies reported lower correlation coefficients [21], [37][39]. The single best anthropometric predictor for the specific measures of both VAT and CAT appeared to be waist circumference in both sexes, although BMI showed almost equally strong univariate correlations.…”
Section: Discussionsupporting
confidence: 90%
“…Also, MRI analyses are often limited by operator-intensive and time-consuming processes for image analyses. Most previous studies using MRI for adiposity research had therefore included relatively few study participants and/or limited imaging analyses to small anatomical areas such as the abdominal area only [19], [20], or even to single image slices [21], [22]. By developing automated algorithms for the analysis of MRI images (for images based on the Dixon technique) [15], we were able to apply MRI for whole-body measurements of adipose and lean tissue compartments in a relatively large study of 1,192 study participants.…”
Section: Discussionmentioning
confidence: 99%
“…There are also several limitations. Body mass index is a nonspecific measure of obesity because it does not distinguish more metabolically active abdominal fat from other body fat 42 and it does not distinguish whether excess body weight relative to height is attributable to fat or nonfat tissues. 43 However, in the Prostate Cancer Prevention Trial, associations of obesity with prostate cancer risk were stronger for BMI than any measure of central adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal adipose tissue compartments were estimated from a single axial slice at the umbilical level, as it has been shown that measurements in this slice are representative for the total amount of VAT location [29]. This slice was reconstructed from the 3D VIBE-Dixon images which were assessed in coronal direction.…”
Section: Methodsmentioning
confidence: 99%